Polysaccharide/Drug Nanocomposite Fabrication And Their Interaction With Cancer Cell Lines In-Vitro - Hammouda, Samia (AUC Knowledge Fountain, 2026)
Tamoxifen (Tam) remains a cornerstone in breast cancer therapy; however, its clinical effectiveness is often limited by poor aqueous solubility, systemic side effects, and insufficient drug localization. This thesis addresses these challenges through the rational design, optimization, and comparative evaluation of polymeric drug delivery systems aimed at improving Tam solubility, release control, and therapeutic selectivity. Two complementary delivery platforms were investigated: tamoxifen-loaded polycaprolactone/chitosan nanoparticles (Tam-PCL-Cs-NPs) and tamoxifen-loaded nanofiber (NF) systems based on polyvinyl alcohol (PVA) and polycaprolactone (PCL). A Quality by Design (QbD) approach was applied to optimize the nanoparticle formulation using Plackett–Burman and Box–Behnken designs. The optimized Tam-PCL-Cs-NPs exhibited nanoscale size, narrow size distribution, and sustained biphasic drug release, resulting in enhanced anticancer activity against hormone-responsive (MCF-7) and triple-negative (4T1) breast cancer cell lines, while maintaining acceptable biocompatibility with normal cells. In addition, the nanoparticles (NPs) demonstrated antibacterial activity, supporting their multifunctional therapeutic potential. Localized Tam delivery was further explored using PVA- and PCL-based NF systems. Both platforms successfully encapsulated Tam in an amorphous state and produced fibers with dimensions comparable to native extracellular matrix structures. Polymer hydrophilicity strongly influenced physicochemical and biological behavior. PVA-based NFs enabled rapid drug release and stronger short-term anticancer effects but showed reduced selectivity toward cancer cells. In contrast, PCL-based NFs provided superior thermal stability, controlled biphasic release, and improved biocompatibility with normal fibroblasts. Incorporation of Tam-loaded NPs into PCL-based NFs further prolonged drug release under acidic conditions representative of the tumor microenvironment and enhanced tumor-selective delivery. Overall, this thesis demonstrates that polymer composition, delivery architecture, and nanoparticle integration are decisive factors in optimizing tamoxifen delivery. While PVA-based systems are suitable for applications requiring rapid therapeutic action, PCL-based nanoparticle–nanofiber composites emerge as more promising platforms for sustained, localized, and safer breast cancer treatment, providing a robust foundation for future in-vivo validation and translational development.